Beyond Cognitive Skills: Humanistic Educational Philosophy in Elementary Reading Literacy - Lailatul Husna; Maemonah Maemonah (Journal of Elementary Education Research and Practice, 2026)
This study aims to reconceptualize elementary reading literacy through a humanistic educational perspective by examining how affective and experiential dimensions shape literacy development. While reading literacy is commonly viewed as a cognitive and technical skill, emerging evidence suggests the importance of integrating emotional, relational, and contextual aspects of learning. This study employed a systematic qualitative content analysis of 26 selected articles published between 2020 and 2025, following procedures inspired by the PRISMA framework. The findings reveal that autonomy, empathy, and meaningful learning function as key humanistic dimensions that influence reading literacy through affective engagement and experiential meaning. These dimensions act as mediating mechanisms linking pedagogical practices to literacy outcomes, including reading engagement, comprehension, and identity. The study proposes a humanistic mediation model that provides a conceptual explanation of how literacy development occurs beyond cognitive processes. The findings highlight the need for more student-centered, relational, and contextually relevant literacy instruction in elementary education. This study extends existing literacy frameworks by offering a more holistic and humanistic understanding of reading literacy and provides a foundation for future empirical research.